Clinically Meaningful Improvements in LUTS/BPH Severity in Men Treated with Silodosin Plus Hexanic Extract of Serenoa Repens or Silodosin Alone. Issue 1 (December 2017) - Boeri, Luca; Capogrosso, Paolo; Ventimiglia, Eugenio; Cazzaniga, Walter; Pederzoli, Filippo; Moretti, Donatella; Dehò, Federico; Montanari, Emanuele; Montorsi, Francesco; Salonia, Andrea
Abstract To assess the rate and predictors of clinically meaningful improvements (CMI) in patients with lower urinary tract symptoms (LUTS) treated with either silodosin (SIL) alone or with a combination of SIL+ serenoa repens (Ser) hexanic lipidosterolic extract for ≥12 months. Data from 186 patients were collected. Patients completed the International Prostatic Symptoms Score (IPSS) at baseline and at follow-up assessment. Descriptive statistics and logistic regression models tested rates and predictors of CMI. Two CMI were assessed: 1) >3 points improvement in total IPSS from baseline to end (CMI#1); 2) >25% IPSS improvement from baseline to end (CMI#2). Overall, 93 (50%) patients were treated with SIL and SIL+ Ser, respectively. At a mean 13.5-mos follow-up [range: 12–20], mean IPSS scores were significantly lower in patients treated with SIL + Ser compared to those after SIL (p = 0.002). SIL + Ser patients more frequently achieved CMI#1 (69.9% vs. 30.1%, p = 0.001) and CMI#2 (68.8% vs. 31.2%, p < 0.001) compared SIL men. At multivariable analyses, younger age, IPSS severity and SIL + Ser (all p < 0.03) were independent predictors of CMI#1 and CMI#2. In conclusion, SIL + Ser therapy was more effective than SIL alone in improving IPSS scores in men with LUTS. SIL + Ser treatment led to CMIs in up to seven out of ten men.